Republic of Palau : 2010 Article IV Consultation; Staff Report; a Public Information Notice; and a Statement by the Executive Director of the Republic of Palau on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
The key findings of the Republic of Palau's 2010 Article IV Consultation shows that the single most important issue in Palau remains fiscal policy, including its effect on medium-term growth, as fiscal consolidation proceeds. The global financial crisis followed on the heels of a massive terms-of-trade shock, leading to a sharp curtailment of foreign direct investment and private credit. Tourism tumbled following an airline bankruptcy, and construction activity fell as major infrastructure projects reached completion.